Pemanfaatan Teknologi Informasi Dan Komunikasi Sebagai Media Pembelajaran Pendidikan Agama Islam Pada Masa Pandemi Covid-19 - Nikmatur Ridha; M. Marhaban Ramadhan; Suhendra Suhendra; Tri Abdi Syahputra (-, 2021)
The emergence of the corona virus outbreak that has hit Indonesia has changed in all aspects of people's daily activities. No exception in the world of education, basically the teaching and learning process carried out face to face in class is now switching remotely (online). This is done to prevent the spread of the covid-19 virus l. Therefore, based on research using qualitative methods with this literature study approach. The results found that the use of information and communication technology as a medium for PAI learning during the covid-19 pandemic was an excellent innovation in delivering material to students remotely in an efficient and effective manner. Types of information and communication technology applications that can be used to keep learning going include whatsapp, google meet, zoom, classroom, and youtube. The learning media was chosen by looking at the affordability of students in using the media. As for the functions of the media that can be felt by educators and students in online learning, among others: in the delivery of material in the learning process can be uniformed, the learning process can take place without any time and place limitations, and learning is more interactive by applying learning theory.